Available aerial phytomass of a Poa ligularis and Piptochaetium napostaense grassland during the period 1984-1985 (Semiárida, 2020)
In the rolling country of La Pampa province Lat. 36°39' S - Long. 64°39' W Ea. La Baya Vieja - Dpto. Toay, we determine standing Crop of a natural grassland along a year. From May to November aerial dry phytomass ranged between 101 to 179 gDM/m2. From January to April it ranged 180 to 223 gDM/m2. Poa ligularis y Piptochaetium napostaense were the principal species. They had 100% of annual frequency the first had 31 pl/m2, the second only 19 pl/m2. The contribution of Bothriochloa springfieldii y Rhynchosia senna, two summer species, was low during the year.
Keywords: grassland